A hybrid method for occupations selection in the bio-circular-green economy project of the national housing authority in Thailand - Phurksaphanrat, Busaba; Panjavongroj, Saruntorn (Decision Making: Applications in Management and Engineering, 2023)
The National Housing Authority (NHA) in Thailand has developed a new project with the aim of sustainable development based on the Bio-Circular-Green (BCG) economy for improving the quality of life of people in the country. It not only provides houses to live in but also promotes income generation by choosing and promoting the appropriate occupations for the people. Choosing appropriate occupations within the BCG economy is a complex decision-making process, as there are likely to be many factors to consider for each community. To, address this challenge, a novel hybrid approach combining the Fuzzy Logarithmic Full Consistency Method (FUCOM-LF) and the Combined Compromise Solution (CoCoSo) is introduced. This hybrid method effectively evaluates the sustainability of different occupations and identifies appropriate occupations for the community by ensuring full consistency in weighing the relevant criteria and high-resolution discrimination of alternatives. The proposed comprehensive BCG occupation selection framework serves as a general framework for NHA that can be applied to any community. Additionally, this research provides a compilation of support guidelines for each occupation. Through a case study community, the practicality and effectiveness of the hybrid method and the proposed framework in selecting the appropriate occupations are demonstrated.